THE EXPLANATION AND WORKSHOP ON WASTE MANAGEMENT OF HOUSEHOLD IN KUEH VILLAGE LHOKNGA DISTRICT - Septiani, Riza; Adamy, Aulina; Ramadhaniah, Ramadhaniah (Universitas Muhammadiyah Aceh, 2021)
Improvement of awareness and participation of the community regarding waste management is carried out through efforts in increasing knowledge, facilitating and enabling community to manage waste independently. Therefore, the community will be empowered in building a healthy and sustainable environment. Community service activities was implemented in February 2020 including health education regarding waste management and workshop related to waste sorting practices as well as composting activity using organic waste/household waste and reprocess waste from used plastic bags. The activities was carried out in Meeting Hall, Kueh Village, Lhoknga District, Aceh Besar. Majority of participants are housewives and young adult women in Kueh Village. The main content of activities is waste management that are applicable at community level or in household settings, thus these activities increase community awareness about environmental health problems and empowering them to manage organic waste into compost and reuse plastic bags by reprocessing them into varied goods. Keywords: waste management, organic waste, environmental health, community empowerment, reduce reuse recycle (3R)